A Model for Improving Diet Quality within Child Nutrition Programs: The U.S. Army’s Child and Youth Services Healthy Menu Initiative - Hanson, Jennifer Ann; Joyce, Jillian; Laursen, Denise; Paez, Paola (My University, 2020)
The U.S. Army’s Child, Youth, and School Services (CYS), which has the capacity to serve more than 70,000 meals/snacks per day, is a geographically dispersed system with facilities worldwide. This case report is a description and evaluation of the implementation of a major food program initiative within the CYS system. In collaboration with Kansas State University, the Healthy Menu Initiative was established to standardize the system’s menus, reflect the guidance contained within the 2015–2020 Dietary Guidelines for Americans, and take into account the Child and Adult Care Food Program regulations that went into effect on 1 October 2017. Food storage space, food service equipment, product availability, food safety considerations, and staff shortages have all proven to be challenges in the development and implementation of the menus. Participant acceptance has been an issue in some instances, and special diet requirements add to the workload of the staff. To overcome these challenges, input was solicited from CYS management, care providers, food service staff, and participant families, as well as participants themselves. Taste testing and classroom cooking activities have been developed to increase acceptance, and over 500 CYS food program staff have attended in-depth training sessions to support the initiative. Overall, the initiative has been well received, and there has been an improvement in the diet quality of the foods served within the program. This improvement is noteworthy, as optimal growth and development during childhood and adolescence are reliant on sound nutrition.
Keywords: Child nutrition; Healthy eating index; Menu planning; Food service